2022
DOI: 10.21037/qims-21-292
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of ischiofemoral impingement via a clinical test using hip triaxial dynamic magnetic resonance imaging

Abstract: Background: The present study aimed to use magnetic resonance (MR) to explore the dynamic changes of the ischiofemoral space (IFS) under the triaxial motion of the hip joint and verify the clinical test mechanism for ischiofemoral impingement (IFI).Methods: A prospective design was used to screen 37 patients with clinically confirmed IFI, which included a total of 67 lateral hips, and 39 healthy controls with a total of 69 lateral hips. A dynamic MR examination was performed in positions designed by a simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results show that the largest ischiofemoral space measurement occurred with the hip in the abduction and internal rotation (51.8 mm; 95% confidence interval [CI], 49.2–54.5 mm), whereas hip adduction and external rotation resulted in the narrowest ischiofemoral space measurement (30.8 mm; 95% CI, 25.5–36.0 mm). Li and his colleagues ( Li et al, 2022 ) used repeated MRI to examine IFS and QFS in different positions. They found that the IFS and QFS were significantly reduced in the prone with backward extension and adduction with external rotation positions of the hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the largest ischiofemoral space measurement occurred with the hip in the abduction and internal rotation (51.8 mm; 95% confidence interval [CI], 49.2–54.5 mm), whereas hip adduction and external rotation resulted in the narrowest ischiofemoral space measurement (30.8 mm; 95% CI, 25.5–36.0 mm). Li and his colleagues ( Li et al, 2022 ) used repeated MRI to examine IFS and QFS in different positions. They found that the IFS and QFS were significantly reduced in the prone with backward extension and adduction with external rotation positions of the hip.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratus femoris space could also be evaluated using the ischiofemoral space (IFS) ( Huang et al, 2022 ), which is a bone-to-bone distance indicating the shortest distance between the lateral cortex of the ischial tuberosity and the medial cortex of the lesser trochanter of the femur. However, the traditional measurement methods are based on static methods, such as repeated X-ray, MRI, or CT ( Park et al, 2016 ; Johnson et al, 2017 ; Shoji et al, 2017 ; Li et al, 2022 ), to measure IFS in different postures which do not reflect a complete bone movement process. The walking activity of the hip joint depends on the dynamic interaction between the pelvis and femur, and the changes of the bone-to-bone distance during the movement state can reflect the patient’s movement mechanism more comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to improve the understanding of the pathomechanics in IFI using MRI have demonstrated dynamic, position-dependent changes [ 25 , 26 ]. Vincentini et al investigated the effect of external rotation on IFS dimension with kinematic MRI.…”
Section: Discussionmentioning
confidence: 99%
“…They reported narrowing of the IFS in the supine position when moving from 30° internal rotation (25 ± 7 mm) to combined adduction and external rotation (11 ± 3 mm). In addition, they also reported narrowing of the IFS in the prone position during 30° extension (9 ± 3 mm) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%